ESTIMASI STOK KARBON MANGROVE DI MUARA SUNGAI KUMBE DISTRIK MALIND KABUPATEN MERAUKE - Reny Sianturi; Siti Masiyah (Faculty of Agriculture Musamus University, 2018)
Forests reduce and store CO2 through a process of